THE INFLUENCE OF QUALITY OF HUMAN RESOURCES SERVICES AND STUDENTS 'INVOLVEMENT OF STUDENTS' COGNITIVE LEARNING OUTCOMES (STUDY ON STIE SUTAATMADJA AND KOLEJ UNIVERSITI ISLAM ANTARBANGSA) - Nenden Maulida Yuliawati; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2019)
The purpose of this study was to determine whether there was an influence or not from the quality of human resource services and student involvement on student cognitive learning outcomes. The approach used is multiple linear regression, based on the T test and F test for data processing. The main finding is the effect found to assess student cognitive learning outcomes. The results of this multiple linear regression approach provide specific guidance for educational institutions in improving student cognitive learning outcomes.